New taxa and record of mite family Microdispidae (Acari: Heterostigmata) from alpine New Zealand. Issue 3 (2nd April 2016) - Khaustov, A. A.; Minor, M. A.
ABSTRACT: A new monotypic genus Paraphyllodispus Khaustov and Minorgen. nov . (Acari: Pygmephoroidea: Microdispidae) with type species P. vulgaris sp. nov ., and new species Phyllodispus undulatus Khaustov and Minorsp. nov . and Microdispus ( Microdispus ) montanus Khaustov and Minorsp. nov . are described from alpine zone (1600–1900 m a.s.l.) of the Central Otago region of the South Island of New Zealand. Dolichodispus angustus (Krczal, 1959) is also recorded from New Zealand for the first time.